Parental supervision and child injuries. (1st March 2011) - Andrade, C
Abstract : This study examined the relationship between child injury history, family and parents characteristics, and supervision. We applied a Portuguese version of the Parent Supervision Attributes Profile Questionnaire-PSAPQ (Morrongiello & House, 2004 ; Morrongiello & Corbett, 2006 ). One hundred and seventy one parents (42 fathers and 129 mothers) (M=32.94yrs, SD=6.75) completed PSAPQ and a questionnaire about their children injury history, relative to 96 boys and 75 girls (M=3.93yrs, SD=0.99). Parents declared that 92% of their children had small injuries in the last year. Moderate and serious injuries were less frequent. The gender of the child and the family structure did not influence the frequency or the type of injuries. Families with more than four people in the household had children that suffered a greater number of injuries (t(169)=2.07, p=.040) and more serious injuries (χ 2 (3)=12.99, p=.005). Parents of these families showed higher levels of risk tolerance (t(169)=2.86, p=.005). Parents with a college graduation had lower protectiveness (t(169)=3.39, p=.001) and lower supervision values (t(169)=3.64, p<.001) than parents with lower academic qualifications. However, the differences in academic qualification were not correlated with children frequency or type of injuries. The results show that some family characteristics influence the child injury history and the parents' supervision style.